Lung microbiota of raccoon dogs (Nyctereutes procyonoides) using high-throughput sequencing - Li, Wei; Li, Xin; Cheng, Jingran; Liu, Jie; Liu, Jinjun; Wang, Yu; Yuan, Wanzhe; Ren, Erjun (Frontiers in Microbiology, 2025)
Pneumonia frequently causes mass mortality in raccoon dogs, resulting in significant economic loss. Additionally, raccoon dogs carry various zoonotic pathogens. This study systematically assessed pulmonary pathogens in raccoon dogs and their potential public health implications utilizing 2bRAD microbiome sequencing (2bRAD-M) and viral metagenomics. We analyzed 30 lung tissue samples for microbial composition. Sequencing revealed Pseudomonadota, Ascomycota, and Actinobacteria as dominant phyla and Acinetobacter, Escherichia, and Klebsiella as predominant genera. The most abundant species were Acinetobacter baumannii, Escherichia coli, and Klebsiella pneumoniae. In total, 158 species across 84 genera were identified, including 49 potentially zoonotic species. Viral metagenomics revealed Peduoviridae, Rountreeviridae, and Parvoviridae as dominant families, with Valbvirus ValB1MD2, Andhravirus andhra, and Amdoparvovirus carnivoran3 comprising over 80% of the viral composition. These findings highlight the pathogenic complexity of raccoon dog pneumonia and its zoonotic risks, providing crucial insights for disease control and public health management.